FibroSURE and elastography poorly predict the severity of liver fibrosis in Fontan‐associated liver disease. (12th August 2018) - Schachter, Jessica L.; Patel, Manisha; Horton, Samuel R.; Mike Devane, A.; Ewing, Alex; Abrams, Gary A.
Abstract: Objective: As the population of patients with Fontan circulation surviving into adulthood increases, hepatic cirrhosis has grown to be a significant cause of morbidity and mortality. Early detection of advanced hepatic fibrosis is imperative for proper intervention and consideration for heart or combined heart/liver transplantation. Noninvasive biomarkers and elastography have been evaluated for their diagnostic utility with variable results in the Fontan population. Design: The cohort included 14 patients age 26.4 SD 7.5 who underwent Fontan surgery. All patients were evaluated with FibroSURE, shear wave elastography (SWE), hepatic duplex sonography, and liver biopsy. Liver fibrosis on biopsy was evaluated according to the congestive hepatic fibrosis system. Results: In our cohort, 100% of patients had fibrosis with 36% demonstrating advanced fibrosis. FibroSURE agreed with liver biopsy in only 5 out of 14 cases (36%): underestimating in 7 and overestimating in 2 individuals. SWE agreed with liver biopsy in 0% of cases: overestimating in 10 and underestimating in 4 cases. None of the duplex sonography indices predicted the presence or severity of liver fibrosis. Conclusion: This study demonstrates that children who have undergone a Fontan procedure universally develop some hepatic fibrosis and a significant number have advanced fibrosis by adulthood. The FibroSURE blood test, SWE, and hepatic duplex sonography were unable to accurately predict the presence or severity of hepatic fibrosis when compared with liver biopsy. Further studies are needed to investigate novel noninvasive methods and/or biomarkers that can adequately detect advanced hepatic fibrosis before the development of cirrhosis and hepatic decompensation.